Feminizam i žene beat-generacije - Damir Španić ([sic], 2019)
For many years literary theorists considered that women writers of the Beat Generation were not worth mentioning. Being present and absent at the same time, these women remained invisible in popular as well as academic reviews in the Beat Generation literature until the nineties. Today, however, it is crystal clear that the literature of the Beats, even with its distinct misogynistic features, had strong influence on several generations of women writers and artists who have written and performed within the feminist frame. Here we will discuss the women of the Beat Generation who in the early sixties, as insiders within a seemingly male group, started expressing themselves within feminist discourses, through which they sought to free women from the socially imposed roles. The main weapon of the Beat Generation’s fight against globalization, conformism, and class inequalities was the freedom of mind, and this particular mind of beatniks was used by women Beat writers in order to question the social model of gender and sex. By overtaking the spirit of defiance and resistance of the Beats, these authors assigned a new meaning to the term Beat by breaking the mainly masculine definition of the Beat Generation.